North-South Knowledge Sharing on Incentive-based Conditional Cash Transfer Programs - Aber, Lawrence; Rawlings, Laura B. (World Bank, Washington, DC, 2017)
Over the last decade, Conditional Cash Transfer (CCT) programs have become one of the most widely adopted anti-poverty initiatives in the developing world. Inspired particularly by Mexico's successful program, CCTs are viewed as an effective way to provide basic income support while building children's human capital. These programs have had a remarkable global expansion, from a handful programs in the late 1990s to programs in close to 30 countries today, including a demonstration program in the United States. In contrast to many other safety net programs in developing countries, CCTs have been closely studied and well evaluated, creating both a strong evidence base from which to inform policy decisions and an active global community of practice. This paper first reviews the emergence of CCTs in the context of a key theme in welfare reform, notably using incentives to promote human capital development, going beyond the traditional focus on income support. The paper then examines what has been learned to date from the experience with CCTs in the South and raises a series of questions concerning the relevance and replicability of these lessons in other contexts. The paper concludes with a call for further knowledge sharing in two areas: between the North and South as the experience with welfare reform and CCTs in particular expands, and between behavioral science and welfare policy.